Preparation of Carbon Nanotubes-Supported CuMn2O4 Nanocomposites for Highly Efficient Degradation of Methylene Blue Dye - Chen, Xuyi; Chen, Tianlu; Fathy, Nady; Tao, Yousheng (Recent Innovations in Chemical Engineering, 2023)
Background: Waste water containing dyes causes serious environmental problems in both aesthetic and toxicological aspects. Although physicochemical and biological treatment processes have been investigated, functional materials are highly demanded for improving the removal efficiency of dye from wastewater. Objective: To synthesize a heterojunction nanocomposite of CuMn2O4/carbon nanotubes (CNTs) with outstanding catalytic performance for the effective degradation of methylene blue (MB) dye. Methods: Copper manganese oxide-carbon nanotubes (CuMn2O4/CNTs) nanocomposite was prepared by a solvothermal method. The structure and morphology of the samples were characterized with X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), transmission electron microscopic (TEM), and nitrogen adsorption/desorption on the samples at 77 K. The degradation of methylene blue dye was studied using the prepared nanocomposite as a catalyst. Results: CuMn2O4 of small particles was loaded on CNTs, forming a porous structure with a specific surface area of 43.5 m2/g and a total pore volume of 0.17 cm3/g. The optimum conditions for achieving full breakdown in 10 minutes are 1g/L of catalyst dosage and a range of initial concentrations at 50-100 mg/L of MB dye at pH 4. Conclusion: The synthesized CuMn2O4/CNTs nanocomposite exhibited a good prospect as catalyst materials for the decontamination of wastewater polluted with dyes.
Keywords: degradation